TEMPERATURE DEPENDENCES OF THE INITIAL PERMEABILITY OF LITHIUM-TITANIUM FERRITES PRODUCED BY SOLID-STATE SINTERING IN THERMAL AND RADIATION-THERMAL MODES - Surzhikov, A.P.; Malyshev, A.V.; Lysenko, E.N.; Stary, O. (KU Publ., 2022)
The paper investigates the features of phase and structural transformations in lithium-titanium ferrites with regard to the time and temperature of solid-state sintering in thermal and radiation-thermal modes. These properties are studied with using the temperature dependence of the initial permeability. It is shown that electron beam exposure during solid-state sintering sharply accelerates the dissolution of impurity inclusions in ferrites. Also phase homogeneity of lithium-titanium ferrites products increase. The obtained results can be used for increasing of the phase homogeneity in ferrite production.
Keywords: lithium ferrites; solid-state sintering; electron beams; high temperatures; initial permeability